(untitled) (Journal of Applied Learning and Teaching, 2018)
Su and Wood have assembled some excellent chapters in this book that help put frameworks and clarity around some of these issues. After a well-researched introduction, the book is divided into three sections: the first being the development of some theoretical underpinnings to academic leadership; the second a series of narratives from experienced and largely successful academic leaders; with the final section devoted to a discussion of some future directions. The introduction by Su and Wood explores the notion of a cosmopolitan outlook on academic leadership. They view academic leadership as “relating directly to the core academic functions of teaching and learning, research and services, as distinct from the managerial aspects of leading higher education institutions such as financial and strategic planning, marketing and human resource management” (1). They propose a view of cosmopolitanism focused on ‘relationality’ and ‘interconnectivity’. Their view is formed after consideration of the etymology of the word tracing back to the Stoic philosophers where a person was seen as inhabiting “two worlds, a local and a wider community, seeing the individual as belonging to the wider world of humanity” (3). Paraphrasing the environmental movement: Think global. Teach local.